Cardiopulmonary hemodynamic consequences of motor seizure activity in the kainic acid model of temporal lobe epilepsy - Rhodes, Jann, author; McMurtry, Ivan F., committee member; Sawyer, H. R., committee member; Tucker, Alan, advisor; Dudek, F. E., committee member (Colorado State University. Libraries, 2002)
Epilepsy is a generic term applied to a group of chronic conditions characterized by recurrent epileptic seizures; however, few animal models have been successful in modeling the chronic, spontaneous nature of human epilepsy. Individuals with epilepsy also have a higher death rate than the population at large, with 10-17% of these deaths occurring for unexplained reasons. Studies in which cardiopulmonary and seizure activity have been monitored simultaneously are limited and, in the case of animals models, are restricted to the period of time immediately following chemically-induced seizures often in animals that are anesthetized, intubated, and paralyzed. Thus, the relevance of these studies to spontaneous motor seizure activity in humans is questionable. These studies were undertaken to characterize the cardiopulmonary hemodynamic consequences of acute and chronic kainic acid-induced spontaneous motor seizure activity in the kainic acid model of temporal lobe epilepsy. In addition, the effect of mild altitude exposure (10,000 ft., Pb = 525 mm Hg) on seizure frequency was evaluated to determine if a mild, stress (e.g. hypoxia) alters seizure occurrence via a decrease in overall activity.

The first study evaluated the acute effect of multiple, systemic, low-dose injections of kainic acid and multiple, generalized motor seizures on systemic and pulmonary hemodynamics, and addressed the potential application of this model in the study of sudden unexplained death and neurogenic pulmonary edema. We hypothesized that mean systemic (mSAP) and pulmonary (mPpa) pressure, and heart rate would increase during acute, hourly intraperitoneal injections of kainic acid as well as during kainic acid-induced motor seizures. At the end of 4 h, mSAP, mPpa, and heart rate remained relatively unchanged or were slightly lower than baseline values in the control rats. Marked systemic hypotension and bradycardia was observed in all the kainate-treated animals after the first injection. One of two distinct mPpa responses was provoked by the initial kainic acid bolus. mPpa increased in half of the animals within minutes of the 1st injection while mPpa decreased in the other half of the group. With the onset of seizure activity, interictal mSAP and mPpa increased gradually with spikes in pressure accompanying each motor seizure. Heart rate also increased gradually; however, ictal responses were more variable with both tachycardic and bradycardic responses. With the α receptor antagonist phentolamine, mSAP fell, heart rate increased, and ictal mSAP spikes were attenuated. Ictal mPpa spikes were slightly attenuated with phentolamine; however, overall mPpa in the kainic acid-treated group was no different than that recorded prior to the phentolamine injection. Histologically, there was no evidence of pulmonary edema in either group. Simultaneous monitoring of neurological activity via in vivo electrophysiological implants and mSAP, mPpa, and heart rate are needed to assess the mechanism(s) regulating the initial cardiopulmonary responses noted in this study. The initial mPpa response was inconsistent and the increase in mPpa that accompanied overt seizure activity was unaffected by phentolamine suggesting the involvement of non-adrenergic vasoactive mediators. Therefore, additional systematic pharmacological studies are needed to delineate the mechanism(s) regulating pulmonary vascular reactivity in this model.

The majority of data to date regarding the cardiopulmonary effects of seizure activity has been collected during acute administration of chemical convuisants. Therefore, we used the protocol described in the first study to induce chronic seizure activity in a group of rats and subsequently evaluated the cardiopulmonary effect of spontaneous motor seizure activity and the effect of hypoxia on these responses. We hypothesized that mSAP, mPpa, and heart rate would increase during spontaneous seizure activity in kainic acid-treated animals and, that these responses would be exacerbated under acute hypoxia (5 min, 10% 02), moderate hypoxia (2 h, 12-14% 02), and attenuated by the aantagonist phentolamine. Systemic and pulmonary pressures were monitored continuously for 8 h to record pressure changes under normoxic and hypoxic conditions and during spontaneous seizures that occurred during the protocol. Baseline hemodynamic parameters were not significantly different between control and kainic acid rats; however, under the physiological stress of hypoxia, significant differences between the two groups with regard to stroke volume, mPpa, and pulmonary vascular resistance were evident. With phentolamine, mPpa and were exacerbated under normoxia and both hypoxic challenges. With seizure onset under normoxic conditions, mSAP and mPpa increased and heart rate decreased immediately. With seizure onset under hypoxic conditions and normoxic and hypoxic conditions with phentolamine, the relative increase in mPpa was exacerbated while mSAP was attenuated. Overall, the disparity between the control and kainic acid-treated rats in response to hypoxia suggests some degree of autonomic or myocardial dysfunction in the kainic acid animals. The systemic vascular responses noted in this study were mediated primarily via altered adrenergic activity as mSAP was attenuated by phentolamine. The exacerbation of the mPpa and pulmonary vascular resistance with phentolamine suggests the involvement of other, non-adrenergic mediators such as, nitric oxide and endothelin or, reflects permanent vascular damage incurred during the initial kainic acid exposure. A carefully planned pharmacological study is needed to further evaluate the pulmonary vascular responses noted in this model.

Endogenous circadian rhythms, such as the light-dark and sleep-wake cycles and behavioral circumstances affect some forms of epilepsy by inhibiting neuronal excitability. In the kainic acid model of temporal lobe epilepsy, seizures appear to coincide with the activity or degree of inactivity rather than with the light-dark cycle. We hypothesized that seizure occurrence (i.e. frequency) would increase in kainic acid-treated rats during exposure to moderate hypobaric hypoxia and that the increase in seizure frequency would be inversely related to activity level. As anticipated, all rats were more active at night than during daylight hours; however, the kainic acid-treated rats were significantly more active than the control rats at both time points and under all conditions. Seizure frequency in the kainic acid-treated rats with previous documented seizure activity increased hypoxia and remained elevated during the normoxic recovery. However, the increase in seizure frequency was not associated with a hypoxiainduced decrease in animal activity. There was a shift toward less ‘severe’ seizures during hypoxia with 2-3 times as many class III seizures recorded during hypoxia than at any other period. The association between behavioral states and seizure activity in this study was clear-cut with the majority of seizures occurring when the animals were inactive despite the fact that the kainic acid-treated animals were significantly more active than control the majority of the time. Hypoxia, however, had a minimal impact on behavior. The greatest increase in seizure frequency in those rats with previous seizure activity occurred during the light phase of the hypoxic period that could perhaps be attributed to an altitudeinduced disturbance in the normal sleep cycle. While it is possible that seizure activity in humans is unaffected by mild altitude exposure, the lack of incidence data may be due to the failure of people with seizure conditions to consider the event unusual especially if the seizure was considered relatively ‘mild’. A more systematic review of altitude-induced changes in seizure patterns is warranted.

In conclusion, this is the first study to document the acute effects of repeated, low-dose injections of kainic acid and kainic acid-induced generalized seizure activity as well as the long-term effect of recurrent spontaneous motor seizure activity in the chronic kainic acid model of temporal lobe epilepsy on the cardiopulmonary system. For the most part, the systemic cardiovascular responses observed in both the acute and chronic kainic acid models are consistent with the responses documented for other acute and chronic seizure models. However, the pulmonary vascular responses recorded here were not consistent and suggests the involvement of additional mediators or perhaps a direct effect of kainic acid on the pulmonary vasculature. Therefore, systematic pharmacological evaluation of the pulmonary vascular responses noted in both the acute and chronic models is warranted. Furthermore, continued evaluation of altitude-induced changes in seizure patterns, possibly as part of the overall acute mountain sickness syndrome, is suggested, especially in people with a documented history of seizures.
Keywords: neurology; anatomy and physiology; animals